Electric Field‐Responsive Nanopores with Ion Selectivity: Controlling Based on Transport Resistance. Issue 5 (4th April 2016) - Zhu, Yudan; Ruan, Yang; Wu, Ximing; Lu, Xiaohua; Zhang, Yumeng; Lu, Linghong
Abstract: Using external stimuli to control ionic transport behavior in nanopores is an important focus of nanodevice research allowing numerous potential applications. A novel strategy was investigated to control ionic‐transport resistance responses to the electric field intensity in a nanopore and regulate ionic selectivity. Molecular simulations were performed to examine the transport behaviors of K + and Na + in a carbon nanotube‐based biomimetic nanopore under different electric fields. The responses of the modified group to the electric field intensity induced variations in ionic transport resistance, which then led to improved ionic selectivity. This result indicates that driving force and resistance are simultaneously affected by external stimuli under nanoconfinement. Abstract : A novel design strategy involving molecular simulation is proposed to control ionic transport‐resistance responses to the electric field intensity in a nanopore and regulate K + /Na + selectivity. The responses of the modified groups to the electric field intensity induced variations in ionic transport resistance, which resulted in improved ionic selectivity.